Discovery of Buxaceae in Acre State, southwestern Amazon: First record of this ancient plant family in Brazil - Honório, Mayk; Silveira, Marcos (Phytotaxa, 2024)
The first record of Buxaceae for the flora of Brazil was made during fieldwork at the Rio Acre Ecological Station, Acre State, on the border between Brazil and Peru. This study describes the first record of Styloceras brokawii in the region and distinguishes it from other species within the genus based primarily on leaf and fruit morphology.